Hacker within! Ehrlichia chaffeensis Effector Driven Phagocyte Reprogramming Strategy - Lina, Taslima T.; Farris, Tierra; Luo, Tian; Mitra, Shubhajit; Zhu, Bing; McBride, Jere W. (Frontiers in Cellular and Infection Microbiology, 2016)
Ehrlichia chaffeensis is a small, gram negative, obligately intracellular bacterium that preferentially infects mononuclear phagocytes. It is the etiologic agent of human monocytotropic ehrlichiosis (HME), an emerging life-threatening tick-borne zoonosis. Mechanisms by which E. chaffeensis establishes intracellular infection, and avoids host defenses are not well understood, but involve functionally relevant host-pathogen interactions associated with tandem and ankyrin repeat effector proteins. In this review, we discuss the recent advances in our understanding of the molecular and cellular mechanisms that underlie Ehrlichia host cellular reprogramming strategies that enable intracellular survival.